Enamel hypoplasia in a Mesolithic (5900±100 BC) individual from Woźna Wieś (Poland): a case study - Tomczyk, Jacek; Ostrowska, Agnieszka (Anthropological Review, 2018)
Modern anthropological research includes very sophisticated diagnostic methods. They allow us to obtain information that has not been available so far. The aim of this paper is to analyze, using current microscopic technologies, the Mesolithic dental material of one adult individual from Woźna Wieś (Poland). The present case study will focus on the analysis of enamel hypoplasia. A scanning electron microscope (SEM) was used to count the number of perikymata building on the hypoplastic line. Linear enamel hypoplasia (LEH) was diagnosed only on the right mandibular canine. The time of occurrence of environmental disturbance was estimated between about 4.2 and 4.9 years of age. The occlusal wall built the enamel hypoplasia with no more than three to four perikymata, meaning that the physiological stress had to have occurred over a fairly short period of time (about 30–40 days).